STRATEGIES FOR FINANCING PRIMARY EDUCATION IN AN AILING ECONOMY - Haladu, Abba Abubakar (Sokoto Educational Review, 2020)
Education as an economically and socially productive investment is financed and provided predominantly by the Nigerian government. In recent years, however, adverse macroeconomic conditions and keen intersectoral competition for public funds have reduced most government’s ability to continue managing education which resulted in under-investment in education and with widespread corruption and mismanagement; the collapse of the system is imminent. The paper looked into the importance and state of primary education in the country in consideration of an ailing economy. A history of how primary education was financed in Nigeria was given with an attempt at explaining before and after independence financing and in the second republic. The era of Primary Schools Management Boards and how they fared in the financing was also discussed. Discussed also was the Universal Basic Education programme. Strategies for effective financing of primary education was also given focusing on the role of the three tiers of the government and also through decentralization through private participation, through promoting community schools, coming up with innovative financial schemes, encouraging the contributions of private organizations/individuals and finally, through sourcing assistance from international organizations.